PERANAN KEPEMIMPINAN CAMAT DALAM PENYELENGGARAAN PELAYANAN PUBLIK DI DISTRIK GILOBANDU KABUPATEN TOLIKARA PROVINSI PAPUA - Kogoya, eko; Mandey, Jantje; Ruru, Joorie (Sam Ratulangi University, 2015)
ABSTRACT: Camat leadership role is very important and decisive in realizing the implementation of effective public in the district. In this regard, this research is intended to answer the question how the district head's leadership role in the organization of public services in the District Gilobandu Tolikara Papua Province.Based on the literature review, the district head's leadership role in administering public services seen from several indicators, namely: Head leadership role in setting the public service program, in developing and directing the district government apparatus, in encouraging morale in the sub-district government officials, in enforcing labor discipline government officials districts, to monitor and oversee the implementation of tasks sub-district government officials, in assessing and evaluating the performance of the government paratur districts, and in making efforts to improve the performance of public service.This study uses a qualitative method. Research informants who were interviewed as many as 12 people are Head, Sekcam, 2 section head, 3 person executive staff, and 5 the head of the village / town. Collecting data using interview techniques. While the analysis of data using qualitative analysis techniques interactive model of Miles and Hubernan.Based on the results of the study be concluded as follows: (1) sub-district leadership role in administering public services seen from the indicators mentioned above can already be realized with quite effective in districts Gilobandu Tolikora Regency of Papua Province. (2) Head are quite effective leadership has been able to realize the implementation of public service that is quite effective in Gilobandu district, though not maximized.Based on the results of this penellian then it can be recommended some suggestions as follows: (1) Head needs to take action more effective in moving, foster and oversee the subordinate personnel in public service delivery. (2) Leadership camat in the public service in the District Gilobandu need to be supported by the availability of adequate leadership in the form of budget, facilities and working facilities, as well as support the cooperation of all subordinates.Keywords: camat leadership, public service.